(untitled) (Communications in Mathematical Research, 2021)
Fixed point and common fixed point results for mappings satisfying quasi-contractive conditions expressed in the terms of c-distance on TVS-valued cone metric spaces (without the underlying cone which is not normal) are obtained, and P-property and Q-property for mappings in the terms of c-distance are discussed. Our results generalize and improve many known results.